Downregulation of selective microRNAs in trigeminal ganglion neurons following inflammatory muscle pain - Wei Dong; Ambalavanar Rajini; Bai Guang; Dessem Dean (SAGE Publishing, 2007)
Abstract Active regulation of gene expression in the nervous system plays an important role in the development and/or maintenance of inflammatory pain. MicroRNA (miRNA) negatively regulates gene expression via posttranscriptional or transcriptional inhibition of specific genes. To explore the possible involvement of miRNA in gene regulation during inflammatory pain, we injected complete Freund's adjuvant (CFA) unilaterally into the rat masseter muscle and quantified changes in neuron-specific mature miRNAs in the trigeminal ganglion (TG). Real-time reverse-transcription polymerase chain reaction revealed significant, but differential, downregulation of mature miR-10a, -29a, -98, -99a, -124a, -134, and -183 in the ipsilateral mandibular division (V3) of the TG within 4 hr after CFA. In contrast, levels of tested miRNAs did not change significantly in the contralateral V3 or the ipsilateral ophthalmic and maxillary divisions of the TG from inflamed rats, nor in the ipsilateral V3 of saline-injected animals. The downregulated miRNAs recovered differentially to a level equal to or higher than that in naive animals. Full recovery time varied with miRNA species but was at least 4 days. Expression and downregulation of some miRNAs were further confirmed by in situ hybridization of TG neurons that innervate the inflamed muscle. Although neurons of all sizes expressed these miRNAs, their signals varied between neurons. Our results indicate that miRNA species specific to neurons are quickly regulated following inflammatory muscle pain.